The impact of Filipino Muslim ethnic migration into Sabah on ASEAN integration - Ibnor Azli Ibrahim; Mohd Nur Hidayat Hasbollah Hajimin; Ezad Azraai Jamsari; Badlihisham Mohd Nasir; Mohd Hafiz Safiai (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Migration among ASEAN countries is not new and Sabah is one of the states in Malaysia that faces this phenomenon. Even prior to independence, Sabah had already been receiving immigrants from ASEAN countries. This study aims at analysing Muslim ethnic migration from the Philippines into Sabah and its impact onto ASEAN integration. This study was qualitatively conducted using content analysis instrument and found that the migration has created a multi-ethnic Muslim community in Sabah, making Sabah as an exemplary multi-ethnic state where the different ethnics can live in harmony. Indirectly, Sabah can become a model to other ASEAN countries which have a multiracial population. This is in line with the desirable declaration to form the ASEAN Community. Simultaneously, Sabah can become a link or medium that foster ASEAN inter-member relations, especially between the Philippines and Malaysia in line with the ASEAN community integration agenda.